The linkage between Churg-Strauss syndrome and leukotriene receptor antagonists: fact or fiction? - McDanel, Deanna L (Dove Medical Press, 2005)
Epidemiologic evidence has shown that the worldwide prevalence of asthma is increasing. The leukotriene receptor antagonists (LTRAs) represent a new class of therapy for asthma. They have been developed in the last decade and play a pivotal steroid-sparing role in treating the inflammatory component of asthma. Consequently, reports of Churg-Strauss syndrome (CSS), a rare form of systemic vasculitis, have been recognized as a potential side effect in individuals with moderate to severe asthma on LTRA therapy. The serious nature of this disorder is worthy of prompt recognition by clinicians and aggressive therapy to avoid the subsequent longstanding effects of vasculitis. To validate the postulated linkage between the LTRAs and CSS, this review comprehensively evaluates reported cases in the literature and supports a pathophysiological relationship between the LTRAs and the development of CSS.